Develop an efficient and specific AAV-based labeling system for Muller glia in mice - Yanxia Gao; Kailun Fang; Zixiang Yan; Haiwei Zhang; Guannan Geng; Weiwei Wu; Ding Xu; Heng Zhang; Na Zhong; Qifang Wang; Minqing Cai; Erwei Zuo; et al. (Scientific Reports, 2022)
Abstract Reprogramming Müller glia (MG) into functional cells is considered a promising therapeutic strategy to treat ocular diseases and vision loss. However, current AAV-based system for MG-tracing was reported to have high leakage in recent studies. Here, we focused on reducing the leakage of AAV-based labeling systems and found that different AAV serotypes showed a range of efficiency and specificity in labeling MG, leading us to optimize a human GFAP-Cre reporter system packaged in the AAV9 serotype with the woodchuck hepatitis virus post-transcriptional regulatory element (WPRE) removed. The leakage ratio of the AAV9-hGFAP-Cre-ΔWPRE decreased by an approximate 40-fold compared with the AAV9-hGFAP-Cre-WPRE labeling system. In addition, we validated the specificity of the AAV-ΔWPRE system for tracing MG reprogramming under Ptbp1-suppression and observed strict non-MG-conversion, similar to previous studies using genetic lineage tracking mouse models. Thus, the AAV9-hGFAP-Cre-ΔWPRE system showed high efficiency and specificity for MG labeling, providing a promising tool for tracing cell fate in vivo.